Odpowiedź :
[tex]Zad. 1\\Wzor: h=\frac{a\sqrt3}2\\a)\\h=\frac{6\sqrt3}2=3\sqrt3\\b)\\h=\frac{18\sqrt3}2=9\sqrt3\\c)\\h=\frac{21\sqrt3}2=10,5\sqrt3\\d)\\h=\frac{0,8\sqrt3}2=0,4\sqrt3[/tex]
[tex]Zad. 2\\h=\frac{a\sqrt3}2 /*2\\2h = a\sqrt3 /:\sqrt3\\a=\frac{2h}{\sqrt3}\\a)\\a=\frac{2*8\sqrt3}{\sqrt3}=\frac{16\sqrt3*\sqrt3}3=\frac{16*3}3=16\\b)\\a=\frac{2*4\sqrt3}{\sqrt3}=\frac{8\sqrt3*\sqrt3}3=\frac{8*3}3=8\\c)\\a=\frac{2*12}{\sqrt3}=\frac{24\sqrt{3}}3=8\sqrt3\\d)\\a=\frac{2*8}{\sqrt3}=\frac{16\sqrt3}3[/tex]
[tex]Zad. 3\\Wzor: d=a\sqrt2[/tex]
[tex]a)\\d=6\sqrt2cm\\b)\\d=12\sqrt2cm\\c)\\d=3\sqrt2cm*\sqrt2=6cm\\d)\\d=\sqrt6cm*\sqrt2=\sqrt{12}cm=\sqrt{4*3}cm=2\sqrt3cm[/tex]
[tex]d=a\sqrt2 /:(\sqrt2)\\a=\frac{d}{\sqrt2}\\\\a)\\a=\frac{7\sqrt2}{\sqrt2}=\frac{7\sqrt2*\sqrt2}2=\frac{7*2}2=7\\b)\\a=\frac{12}{\sqrt2}=\frac{12\sqrt2}2=6\sqrt2\\c)\\a=\frac{0,6}{\sqrt2}=\frac{0,6\sqrt2}2=0,3\sqrt2\\d)\\a=\frac{8\sqrt6}{\sqrt2}=\frac{8\sqrt6*\sqrt2}2=4\sqrt{12}=4*2\sqrt3=8\sqrt3[/tex]